Sclerosing odontogenic carcinoma presenting in the maxilla of a 64-year-old female: A case report - Leyn B. Shakhtour; Jonathan Tucci; Barbara Murphy; Kim Ely; Michael C. Topf (Oral Oncology Reports)
Sclerosing odontogenic carcinoma (SOC) is a rare intraosseous carcinoma of the jaw which was recently added to the World Health Organization classification of head and neck tumors. We report a case of SOC in the left maxilla of a 64-year-old who complained of several years of midface swelling, facial pain, and facial weakness. Imaging revealed an infiltrative mass and biopsy demonstrated fibrous dysplasia involved by a low-grade carcinoma, undeterminable origin. A partial maxillectomy was remarkable for scattered small, angulated nests and long, thin cords of cuboidal cells infiltrating a markedly sclerotic stroma. Bony changes consistent with fibrous dysplasia were again seen. Immunohistochemically, the epithelial cells were reactive for AE1/AE3 and p63, while negative for ERG and myogenin consistent with odontogenic carcinoma. The disease was not resectable, and the patient was treated with palliative immunotherapy. The diagnosis of SOC requires careful evaluation of clinical and pathologic features.